Sister Death: Political Theologies for Living and Dying - Marovich, Beatrice (Columbia University Press, 2023)
Drawing on a wide range of sources-from Toni Morrison to Derrida to grassroots "death positive" movements-Beatrice Marovich critiques a political theology that pits life and death against each other in a state of endless war. Adapting the figure of "Sister Death" from Saint Francis, she calls for recognizing that life and death are family.